2010
DOI: 10.1007/s11240-010-9704-x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic overexpression of AtmiR398b gene in tobacco influences seed germination and seedling growth

Abstract: MicroRNAs play crucial roles in plant development and growth, nutrient allocation and stress responses by posttranscriptionally regulating their target genes. In the present investigation, RNA blotting studies and stem-loop RT-PCR analysis confirmed the existence, and conserved nature of miR398 in tobacco. The positive accumulation of miR398 in response to copper deficiency provided additional evidence for the involvement of miR398 in plant responses to copper homeostasis. The functional characterization of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…It would be logical to assume that this is due to the heightened activity of miR398 (CSDR-miRNA) under drought conditions in the tolerant rice cultivars. Over-expression of miR398 has been associated with increase in H 2 O 2 levels in tobbaco 87 , rice 88 and common bean 73 . The cultivar-specific decrease in the Cu/ZnSOD activity is also supported by a corresponding increase in the ROS levels in the tolerant cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…It would be logical to assume that this is due to the heightened activity of miR398 (CSDR-miRNA) under drought conditions in the tolerant rice cultivars. Over-expression of miR398 has been associated with increase in H 2 O 2 levels in tobbaco 87 , rice 88 and common bean 73 . The cultivar-specific decrease in the Cu/ZnSOD activity is also supported by a corresponding increase in the ROS levels in the tolerant cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…These two miRs have been postulated to participate in the regulation of seed germination, seedling growth and root length. Prior research showed that overexpression of miR398 and miR408 in transgenic plants inhibited seed germination, seedling growth and root length (Box et al, 2005, Feng et al, 2010. Therefore, the decrease in expression level of miR398 and miR408 in Au ENP-exposed seedlings was possibly responsible for the higher rate of seed germination, seedling growth, and root elongation compared to control seedlings observed.…”
Section: Mechanisms For Metallic Nanoparticle Effectsmentioning
confidence: 97%
“…Stress‐responsive genes including superoxide dismutases were identified as targets of miR398 in Arabidopsis thaliana (Bonnet et al ., ; Jones‐Rhoades and Bartel, ; Beauclair et al ., ). Ectopic overexpression of miR398 in tobacco ( Nicotiana tabacum L.) affects seed germination and seedling growth (Feng et al ., ), suggesting that expression of miR398 is strictly regulated in tobacco plants. As expected, expression of miR398 was faintly detectable in tobacco leaves but strongly induced in leaf‐derived callus cultured on sucrose‐containing medium (Figure a).…”
Section: Resultsmentioning
confidence: 99%